FAKTOR PENYEBAB PELANGGARAN PERATURAN SISWA DI PONDOK PESANTREN MUNTASYIRUL ULUM YOGYAKARTA - Harpan Reski Mulia (Nathiqiyyah, 2020)
This research aims to determine the factors that are the cause of violation of students ' rules in Pondok Pesantren Muntasyirul Ulum Yogyakarta. The method used in this research is a qualitative method, the sampling technique used is snowball sampling with a total of seven people, consisting of four students of Pesantren Muntasyirul Ulum, two teachers Muntasyirul Ulum and one counseling teacher MAN 3 Yogyakarta. The data collection techniques are interviews, observations and documentation. Then, the data analysis Tekknik in this study refers to the concept of Miles and Huberman, namely: data reduction, data presentation, and making conclusions/verifications. The findings of this research show that the three factors that are the cause of the students violate the rules of the school are not self-chosen, less-empowered social interaction, and affected with familiar friends.